Did COVID-19 challenges psychological resilience of pregnant women? an evidence-based review with recommendation - Chakraborty, Betsy (International Journal Of Community Medicine And Public Health, 2021)
Any conflict, extreme stress, emergency situation, natural disaster multiplies mental health hazard. History of Spanish flu outbreak witnesses the damage of pregnant women i.e. as short-term impact inflate the rate of preterm deliveries and the baby’s who were in womb persist the risk of developing medical and psychiatric disorders like diabetes, coronary artery disease, cancer and schizophrenia in future. Pregnant women are considered more vulnerable for COVID-19 as pregnancy makes women prone to respiratory pathogen, which leads to severe pneumonia. Women are three times more prone to anxiety than man. Continuous strict restriction on consultancy visit and gathering, rumors and contradictory information, uncertainty about delivery plan & health of mother and baby indirectly affected women’s emotional and psychological health of perinatal period. Fear and stigma grasps them when anticipating social discrimination and segregation from baby if they become positive. Growing evidence shows psychological impacts i.e. high levels of anxiety, depression and stress are prevalent among pregnant women irrespective of geographical and cultural boundaries across countries like India, China, Canada, UK, Australia and Israel. WHO recommended for adopting holistic approach of care, consideration of major two aspects (i.e. clinical and psychological experiences) in pandemic situations for helping in better positive coping of mother, baby and family members. This present review aimed to find out triggering factors, challenges, major types of psychological issues, consequences of psychological impact among perinatal women due to COVID-19 and want to prescribe evidence-based resolution and preparedness for combating such pandemic situation.